Quality of life in patients with mycosis fungoides and Sézary syndrome: a review of the literature. (October 2021) - Ottevanger, Rosanne; van Beugen, Sylvia; Evers, Andrea; Willemze, Rein; Vermeer, Maarten; Quint, Koen
Abstract : Cutaneous T-cell lymphomas (CTCL) are a rare, heterogenous group of T-cell lymphomas that primarily manifest in the skin. Mycosis fungoides (MF) and Sézary syndrome (SS) are considered the classic types of CTCL. The diverse manifestation of CTCL results in a wide range of symptoms with a possible mild to severe impact on quality of life (QoL) depending on the disease stage. Previous studies on QoL in CTCL patients report diverse patient populations and use many different QoL instruments. In the current literature a clear overview on the influence of the different stages of disease (early MF, late-stage MF/SS or total group) on the QoL is lacking. Therefore, a systematic search of the literature was conducted using the PubMed, Embase, PsycINFO, and Web of Science databases. Studies were included if they described QoL in patients with MF and SS retrieved by 14 standardized instruments or qualitative interviews. In total 24 studies were included using 18 different questionnaires to report on dermatology-specific, cancer-specific, and generic QoL. The effect on QoL was found to be greater in patients with late-stage disease as compared to early-stage disease, with significant impairments on functional, emotional, and physical domains. Nonetheless, even in patients with limited disease, QoL was mildly to moderately affected. Overall, pruritus was the most frequent reported and most bothersome symptom. Significant influence of the disease on daily life activities were found, not only in patients but also on caregivers and family. This broad, structured overview on QoL in MF and SS patients underlines the influence of disease stage on QoL, and therefore recommends future studies to distinguish between disease stages when reporting results. Furthermore, this overview can inform clinicians in clinical practice by creating awareness of QoL deficits according to disease stage.